Analisis Faktor yang Berhubungan dengan Perilaku Pencegahan Infeksi Nosokomial pada Tenaga Kesehatan dan Non Kesehatan di Rumah Sakit - Warella, Juen Carla; Kamoda, Tri Puspa Rini Dusung; Kailola, Nathalie E.; Tahitu, Ritha (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2024)
Nosocomial infections occur in patients and healthcare workers in hospitals during the course of treatment or while working in healthcare facilities. Full awareness is needed, especially for health and non-health workers, to pay more attention to nosocomial infection prevention behaviour. This study aimed to determine the factors associated with nosocomial infection prevention behaviour of health and non-health workers in Rumah Sakit Khusus Daerah (RSKD) Maluku Province in 2023. This study was a quantitative analytical that used a cross-sectional approach. The sampling technique used was total sampling. The results showed that age was not significantly associated with nosocomial infection prevention behaviour with p value (0,097). Meanwhile, the variables length of service, sex, and knowledge were related to preventive behaviour with p value (0.000). Regarding the sex variable, it was found that women had good infection prevention behaviour, with 80.6%, or 54 respondents. In comparison, men had less good infection-prevention behaviour, with a percentage of 43.4% or 13 respondents. The average length of service with good nosocomial infection prevention behaviour was 5-10 years and more than 10 years. In the knowledge variable, 68 respondents (91.9%) had good knowledge, while 20 respondents (87%) had lack of knowledge. Therefore, it was necessary to increase awareness of nosocomial infection prevention behaviours to reduce the incidence of nosocomial infections in hospitals and to ensure the safety of patients, healthcare and non-healthcare workers, and visitors.